Sexual dimorphism in the assessment of mineral apposition rate during osteoporosis (Research, Society and Development, 2021)
The objective of this study was to evaluate the daily maxillary and tibial bone mineral apposition rate of ovariectomized rats and orchiectomized rats through confocal laser microscopy. Twenty-four animals were divided into 4 groups (SHAMF, OVX, SHAMM and ORQ). Six rats were distributed to the SHAMF group (submitted to fictitious surgery); six rats to the OVX group (submitted to bilateral ovariectomy); six rats to the SHAMM group (submitted to fictitious surgery) and six rats to the ORQ group (submitted to bilateral orchiectomy). On the 60th day after the surgical procedures the animals received 20 mg/kg of calcein and after 24 days 20 mg/kg of alizarin red was administered. The euthanasia was performed 18 days after the last fluorochrome administration. The histological slides obtained were submitted to confocal microscopy analysis and then dynamic histomorphometry was performed to obtain the daily mineral apposition rate (MAR). In the tibias, the values of MAR were higher for the SHAMF group (P